NOBLE GASES AS TRACE ELEMENTS IN MAGMATIC PROCESSES - Carroll M.R.; Draper D.S. (My University, 1994)
The abundance and isotopic composition of the trace amounts of noble gases found in magmas provide insights into the large-scale differentiation of the Earth, the origin of the atmosphere, and potentially into the degassing and differentiation of mantle-derived magmas. Unlike most other trace elements whose behavior can be understood from consideration of crystal-melt equilibria, the noble gases may also be partitioned into a magmatic vapor phase. This complicates the interpretation of observed variations in noble gas abundances in magmas, but it also means that noble gas abundances can yield information not obtainable from geochemical studies of non-volatile trace elements (e.g., regarding magma degassing history). Currently available data and theoretical models allow reasonably comprehensive description of how noble gas partitioning between melt and vapor will vary with melt composition, pressure, temperature and the size of the noble gas atom. Partitioning of noble gases between crystals and melt or vapor is not so well understood, and the few data available are contradictory. Some studies suggest that noble gases are highly incompatible in crystals (D < 0.01), while others suggest that crystal-liquid partition coefficients are higher (D > 0.1), and possibly that the heavy rare gases (e.g., Kr, Xe) are more compatible than the lighter rare gases (e.g., He, Ne). Of additional concern is whether defects may play a role in allowing incorporation of electrically neutral noble gases in crystals, especially since noble gas contents of many natural crystals may be in the sub-ppb concentration range. Most data support incompatible behavior for the noble gases but complications arising from adsorption effects, especially for the heavy rare gases, possible siting of noble gases in defects, and concerns about “contamination” of samples by gas-rich fluid inclusions require additional investigation before we can quantitatively model the behavior of noble gas elements during partial melting or during crystal fractionation.